Risk Assessment Regarding Perceived Toxicity and Acceptance of Carbon Dioxide-Based Fuel by Laypeople for Its Use in Road Traffic and Aviation - Engelmann, Linda; Arning, Katrin; Linzenich, Anika; Ziefle, Martina (Frontiers in Energy Research, 2020)
One approach to mitigate the emissions of carbon dioxide (CO2) is the development of CO2-based products, such as fuels for road traffic and aviation. Since the acceptance of sustainable product innovations such as CO2-based fuels depends on an individual’s acceptance decision based on perceived risks and benefits, this study focuses on subjective risk perceptions of fuel toxicity. An online survey was conducted to assess risk evaluations of CO2-based fuels regarding various risk targets, exposure characteristics, negative outcomes for health and environment, and frequency of health impairments. CO2-based fuels were significantly more positively perceived than conventional fuels and were found to be perceived to pose less risks regarding types of exposure and properties leading to toxic effects. For both aviation and road traffic the acceptance of CO2-based fuels increased with decreasing fear of health and environmental consequences and the less frequently health effects were assessed. The findings allow to derive implications for risk assessment and communication strategies in the development and roll-out of CO2-based fuels.